Halal Supply Chain Management: An Analysis of Decision-Making factors at Ngebum Beach in Kendal - Atik Dina Nasikhah; Septian Dwi Cahyo (LP2M IAIN Palopo, 2025)
purpose: The purpose of this study is to determine the factors causing the decline in the number of visitors to Ngebum Beach in Kendal Regency. Furthermore, the researcher will implement Halal Supply Chain Management in the tourism industry by applying the concept of halal tourism at Ngebum Beach in Kendal. The researcher will then analyze whether the implementation of halal supply chain management in the field of halal tourism can be one of the factors that attract tourists to visit Ngebum Beach.Methods: The research method used was qualitative research with a ground theory approach. The data collection techniques used were reduction, data presentation, and drawing conclusions. The data analysis technique used was data triangulation.. Results: The results of the study show that the factor causing the decline in the number of visitors to Ngebum Beach after it became a trending topic was that visitors were no longer curious about Tiram Bakar. The concept of halal tourism was not an explicit factor in tourists' decision to visit, but was based on accessibility, economy, culinary characteristics, and local tourism-based customs.Implications: These findings provide practical insights for Ngebum beach managers and halal guarantee institutions (LBH) that the application of the concept of halal tourism by applying halal tourism categories to tourist destinations cannot be fully implemented, given that each tourist destination has its own attractions and has rules that are enforced in accordance with the conditions at that tourist destination